2016
DOI: 10.1007/s00520-016-3112-7
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and preferences toward monitoring symptoms, distress, and quality of life in glioma patients and their informal caregivers

Abstract: PurposeGlioma patients and their informal caregivers face many challenges in living with the disease and its disease-specific consequences. To better meet their needs, a system to monitor symptoms, distress, and quality of life could prove useful. We explored glioma patients’ and caregivers’ attitudes and preferences toward monitoring in general and specifically toward paper-and-pencil and computerized (eHealth) options.MethodsIn total, 15 patients and 15 informal caregivers participated in individual, semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…This qualitative study is an extension of our earlier report on PBT caregivers' attitudes and preferences toward monitoring care issues [12]. Although PBT caregivers reported to have utilized a range of different formal and informal support services, those who experienced more care issues indicated to have preferred more support.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This qualitative study is an extension of our earlier report on PBT caregivers' attitudes and preferences toward monitoring care issues [12]. Although PBT caregivers reported to have utilized a range of different formal and informal support services, those who experienced more care issues indicated to have preferred more support.…”
Section: Discussionmentioning
confidence: 75%
“…In our previous report on the attitudes and preferences of Dutch glioma patients and their family caregivers regarding monitoring symptoms, distress and QOL issues, we found that although the preferred method for monitoring issues is highly personal, a combination of online and personal care ('blended care') was advised [12]. Importantly, we found that family caregivers viewed monitoring symptoms, distress and QOL (collectively called 'care issues' hereafter) more favorably than patients did.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Rooney et al (2014) demonstrated a design of a "Patient Concerns Inventory" in a neuro-oncological clinic that was more sensitive to the needs and concerns of brain tumour patients than general cancer checklists. Boele et al (2016) found that patients may find some disadvantages of monitoring as it can be time-consuming and may increase awareness of problems they did not know they had.…”
Section: Education and Informationmentioning
confidence: 99%